STUDI KOMPARASI IMPLEMENTASI PENGECUALIAN “BAHAYA DI LAUT” BERDASARKAN HAGUE VISBY RULES DAN HUKUM INDONESIA - Paramita, Kartika; Putri, Zahira Balqis Awina (Penerbit Universitas Atma Jaya Yogyakarta, 2026)
Perils of the sea is an exclusion clause that can exempt sea carriers from liability for cargo damage. This doctrine is globally recognized, including under the preeminent convention in carriage of goods by sea, the Hague-Visby Rules, and the Indonesian Commercial Code. This study aims to compare the interpretation of Indonesian positive law with that of other State parties to the Hague-Visby Rules. Utilizing a qualitative method with a comparative-legal approach, this study finds that Indonesia, as a civil law jurisdiction, tends to equate perils of the sea with the doctrine of force majeure, rather than adopting it as an independent doctrine as commonly implemented in common law jurisdiction. The absence of specific parameters and indicators regarding the implementation of this doctrine within Indonesian domestic law creates legal uncertainty that blurs the line between pure maritime risks and human error mistakes. This loophole potentially undermines the Indonesian maritime commercial climate, as carriers can evade their liability. This study concludes that there is a need for the synchronization of the interpretation of perils of the sea doctrine by Indonesian courts to ensure equitable legal certainty.